The prevalence of diabetes mellitus and hypertension and its effects on healthcare demand among elderly in Malaysia - Shamzaeffa Samsudin; Norehan Abdullah; Shri Dewi Applanaidu (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2016)
Introduction The prevalence of non-communicable diseases (NCDs) in Malaysia shows a rising trend that influences the society in many respects. Country specific evidence is vital for effective intervention. The aims of this study were to identify the role of gender and urbanisation status on NCDs prevalence and its effect on health care demand, specifically doctor visits among elderly in Malaysia. We focused on two of the highest occurrence NCDs in the country – diabetes mellitus and hypertension. Methods A total of 1,414 respondents aged 60 years and above were selected using a multistage sampling for face-to-face interview. We started the analysis with descriptive analysis of the prevalence, taking the effect of gender and urbanisation status of residing area. We extended the study with parametric analysis to find the effect of these health problems on the likelihood of doctor visits as it reflects the equity for access and utilisation issues. Results Results showed that there were no significant difference of prevalence by gender and urbanisation for hypertension and diabetes mellitus. By utilising probit model, we found that those with diabetes mellitus or hypertension, controlling for other variables, were more likely to utilise doctor services. Conclusion This result implies that the prevalence of NCDs may further increase demand for health care, especially in the state with a high proportion of older age groups.